Treatment with Nitrate, but Not Nitrite, Lowers the Oxygen Cost of Exercise and Decreases Glycolytic Intermediates While Increasing Fatty Acid Metabolites in Exercised Zebrafish. Issue 12 (9th September 2019) - Axton, Elizabeth R; Beaver, Laura M; St. Mary, Lindsey; Truong, Lisa; Logan, Christiana R; Spagnoli, Sean; Prater, Mary C; Keller, Rosa M; Garcia-Jaramillo, Manuel; Ehrlicher, Sarah E; Stierwalt, Harrison D; Newsom, Sean A; et al.
ABSTRACT: Background: Dietary nitrate improves exercise performance by reducing the oxygen cost of exercise, although the mechanisms responsible are not fully understood. Objectives: We tested the hypothesis that nitrate and nitrite treatment would lower the oxygen cost of exercise by improving mitochondrial function and stimulating changes in the availability of metabolic fuels for energy production. Methods: We treated 9-mo-old zebrafish with nitrate (sodium nitrate, 606.9 mg/L), nitrite (sodium nitrite, 19.5 mg/L), or control (no treatment) water for 21 d. We measured oxygen consumption during a 2-h, strenuous exercise test; assessed the respiration of skeletal muscle mitochondria; and performed untargeted metabolomics on treated fish, with and without exercise. Results: Nitrate and nitrite treatment increased blood nitrate and nitrite levels. Nitrate treatment significantly lowered the oxygen cost of exercise, as compared with pretreatment values. In contrast, nitrite treatment significantly increased oxygen consumption with exercise. Nitrate and nitrite treatments did not change mitochondrial function measured ex vivo, but significantly increased the abundances of ATP, ADP, lactate, glycolytic intermediates (e.g., fructose 1, 6-bisphosphate), tricarboxylic acid (TCA) cycle intermediates (e.g., succinate), and ketone bodies (e.g., β-hydroxybutyrate) by 1.8- to 3.8-fold, relative to controls. Exercise significantly depleted glycolytic and TCA intermediates in nitrate- and nitrite-treated fish, as compared with their rested counterparts, while exercise did not change, or increased, these metabolites in control fish. There was a significant net depletion of fatty acids, acyl carnitines, and ketone bodies in exercised, nitrite-treated fish (2- to 4-fold), while exercise increased net fatty acids and acyl carnitines in nitrate-treated fish (1.5- to 12-fold), relative to their treated and rested counterparts. Conclusions: Nitrate and nitrite treatment increased the availability of metabolic fuels (ATP, glycolytic and TCA intermediates, lactate, and ketone bodies) in rested zebrafish. Nitrate treatment may improve exercise performance, in part, by stimulating the preferential use of fuels that require less oxygen for energy production.